Performance measurement and management control innovative concepts and practices - Epstein, Marc J.; Manzoni, J. F.; Dávila, Antonio (Emerald, 2010)
In 2001, we gathered a group of researchers in Nice, France to focus discussion on performance measurement and management control. Following the success of that conference, we held subsequent conferences in 2003, 2005, 2007, and 2009. This volume contains some of the exemplary papers that were presented at the most recent conference. Though the conference has been generally focused on performance measurement and management control and has included presentations on many facets of the topic, each year we have also focused on a particular theme of current interest. This year's theme was directed at innovative concepts and practices. This includes creative approaches to solving management challenges of performance and management control and improving organizational performance. It also includes the innovative use of empirical, analytical, experimental, and case-based research. The contents of this book represent a collection of leading research in management control and performance measurement and provide a significant contribution to the growing literature in the area.
Description based on print version record.
Selected conference papers.
Keywords: Management audit -- Congresses.; Managerial accounting -- Congresses.; Organizational effectiveness -- Congresses.; Performance standards -- Congresses.; elektronické knihy; electronic books